Reformy szkolne w pierwszej połowie XIX wieku - Pawelec, Lidia (Biuletyn Historii Wychowania, 2009)
The present text outlines the school reforms carried out in the first half of the nineteenth century. As the timeframe suggests, these reforms were launched and implemented by the then authorities of the Duchy of Warsaw and the Russian authorities administering the Russian part of partitioned Poland. The author attempts to indicate the most important goals and assumptions of the reforms as well as their immediate educational and social consequences. The text is far from being a comprehensive description of the problem but rather serves as an introduction to the substance of the issue under investigation and its political and economic conditioning.